Growth regulators and KNO3 on seed germination of Angelonia salicariifolia - Pinto, A. C.R. [UNESP] (2009)
Angelonia salicariifolia is an herbaceous perennial native to Brazil with ornamental potential as garden plant, cut-flower and potted plant. It has blue flowers 1.0 to 1.4 cm long, in 10-30 cm long terminal racemes. In previous studies seeds of A. salicariifolia showed a positive photoblastic behavior under constant temperatures of 10, 15, 20, 25, 30 and 35°C. The present study evaluated the effects of growth regulators (100, 200, 300, 400, 500 mg L -1 of gibberellic acid and 2.25, 11.3, 22.5 mg L-1 of 6-benzylamino-purine) and potassium nitrate (0.2 and 1.0 %) on promoting its seed germination. The experiment was conducted in a completely randomized design with six replications of 25 seeds, for each treatment. Seeds from dehiscent capsules were sown on one layer of filter paper and moistened with growth regulators or KNO3 solutions. Germination was carried out at 25°C ± 1°C, under continuous light or darkness. Germination (protusion of the radicle) was observed daily for 20 days. In the dark, only gibberellic acid promoted seed germination. The percentage of germination and the speed of germination index at 400 mg L-1 (47.3%; 0.86) and 500 mg L -1 (52.0%; 0.95) were significantly higher compared to 100 mg L -1 (27.8%; 0.38) and 200 mg L-1 (32.3%; 0.49). The mean germination time at 500 mg L-1 (10.0 days) was significantly smaller compared to 100 mg L-1 (11.9 days) and 200 mg L-1 (11.5 days). Under light, treatments did not differ among each other or from the control, except for 22.5 mg L-1 of 6-benzylamino-purine and potassium nitrate (1.0%), which decreased the percentage of germination and the speed of germination index compared to control. The application of growth regulators or potassium nitrate under light condition is not necessary, since these treatments did not improve germination percentage or the speed of germination index.